Biochemical characteristics of a novel protease from the basidiomycete Amanita virgineoides. (28th March 2017) - Yuan, Xianghe; Zhu, Mengjuan; Tian, Guoting; Zhao, Yongchang; Zhao, Liyan; Ng, Tzi Bun; Wang, Hexiang
Abstract: The characterization of a novel protease from Amanita virgineoides is described. The A. virgineoides protease was purified to homogeneity using Q‐Sepharose, carboxymethyl‐cellulose, diethylaminoethyl‐cellulose, and a gel filtration step on Superdex 75. The molecular mass of the purified protease was estimated to be 16.6 kDa. The protease was purified 32.1‐fold, and its specific activity was 301.4 U/mg. The optimum pH was 4.0, and the optimum temperature was 50 °C. Kinetic constants ( K m, V max ) were determined under the optimum reaction conditions, with K m and V max, being 3.74 mg/mL and 9.98 μg mL −1 Min −1, respectively. The activity of the protease was curtailed by Cu 2+, Pb 2+, Fe 3+, Cd 2+, and Hg 2+ ions but enhanced by Mg 2+, Ca 2+, and K + ions at low concentrations. The protease activity was adversely affected by ethylene diamine tetraacetic acid, suggesting that it is a metalloprotease. Four peptide sequences were obtained from liquid chromatography‐tandem mass spectrometry, including KQALSGIR, TIAMDGTEGLVR, VALTGLTVAEYFR, and AGAGSATLSMAYAGAR, which showed 86%, 64%, 60%, and 75% identity with peptides of Hypsizygus marmoreus, Dacryopinax sp. DJM‐731 SS1, Trametes versicolor FP‐101664 SS1, and Paxillus involutus ATCC 200175, respectively. The newly isolated protease showed good hydrolytic activity and biochemical characteristics, which expanded the knowledge of biologically active proteins and provided further insight on this poisonous fungus.